Nobody Is Perfect: Comparison of the Accuracy of PCR-RFLP and KASP™ Method for Genotyping. ADH1B and FTO Polymorphisms as Examples - Hubáček, J A; Pikhart, H; Peasey, A; Kubínová, R; Bobák, M (Folia biologica, 2015)
DNA genotyping is among the most common analyses currently performed in scientific research. Two high-throughput genotyping techniques are widely used - the "classic" PCR-RFLP and probe-based methods such as TaqMan® PCR assay or KASP™ genotyping. The probe-based techniques are claimed to be more accurate than PCR-RFLP; however, the evidence for this claim is sparse. We have directly compared results of genotyping of two SNPs (rs1229984 and rs17817449) obtained by the PCR-RFLP and KASP™ in 1,502 adult Caucasians. The results were identical in 97.3 % and 95.9 % cases, respectively. Discrepancies (either different results or result obtained with one but not with the other method) were addressed by confirmatory analysis using direct sequencing. The sequencing revealed that both methods can give incorrect results, but the frequency of incorrect genotyping of rs1229984 and rs17817449 was very low for both methods - 0.1 % and 0.5 %, respectively, for PCR-RFLP and 0.1 % and 0.3 %, respectively, for KASP™. These results confirm that the KASP™ technique is slightly more accurate, but it achieves slightly lower call rates than PCR-RFLP. When carefully set up, both PCR-RFLP and KASP™ could have accuracy of 99.5 % or higher.
Keywords: Alcohol Dehydrogenase; Polymerase Chain Reaction; Proteins; genotyp; alkoholdehydrogenasa; gen pro FTO; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; polymorfismus délky restrikčních fragmentů; Humans; Genotype; lidé; proteiny; Polymorphism, Restriction Fragment Length; polymerázová řetězová reakce